A Study on the Impact of Social Media Use on Teaching Performance of Teachers in Private Universities in Henan Province—Mediated by Relational Conflict (Architecture Image Studies, 2026)
To explore the impact of social media use on teachers' teaching performance in private universities in Henan Province and its mediating role in relational conflict, this paper uses a sample of 869 teachers from 21 private undergraduate universities in Henan Province. A questionnaire survey was conducted, and descriptive statistics and structural equation modeling were performed using SPSS 27 and Amos 29. This paper categorizes social media use into task-oriented and social-oriented types. Through reliability and validity tests, correlation analysis, and mediation effect tests, it was found that both types of social media use are significantly positively correlated with teaching performance and significantly negatively correlated with relational conflict. Relational conflict plays a partial mediating role between social media use and teaching performance in both types: the indirect effect of "task-oriented use → relational conflict → teaching performance" is 0.127, and the indirect effect of "social-oriented use → relational conflict → teaching performance" is 0.114 (p < 0.001 for both). Ultimately, this paper reveals a dual pathway of "direct empowerment - indirect transmission" in how social media use affects teaching performance, providing empirical evidence for teachers in private universities in Henan Province to optimize their social media use, alleviate relational conflict, and improve teaching performance.